Acetaminophen influence on change of endogenous intoxication indices status of plasmatic membranes in rats with type 2 diabetes mellitus - Furka, Olga; Ivanusa, Iryna; Mykhalkiv, Mariia; Klishch, Ivan (Journal of Education, Health and Sport, 2017)
Introduction: Accumulation of excessive amounts of exo- and endotoxins in the body leads to the inevitable occurrence endogenous intoxication. This status is accompanied by a different type of inflammatory processes in the tissues. Middle mass molecules are products of catabolism of endo- and exogenous proteins. Separate fractions of middle molecular peptides have neurotoxic activity, change the membranes permeability, disturb the sodium-potassium balance, transport amino acids, creatinine excretion, protein biosynthesis, tissue respiration, cause microcirculation disorders, and have cytotoxic activity. Transaminases are enzymes that catalyze biochemical reactions progress. Aminotransferases influence on reaction of the formation and decomposition of amino acids and carbohydrates. The aim of the study: The aim of our work was to study endogenous intoxication and status of plasmatic membranes in animals with type 2 diabetes mellitus and acetaminophen toxic lesions. Research materials and methods: We conducted two series of experiments. In the first series toxic lesion was caused by a single intragastric administration of acetaminophen suspension in 2 % starch solution to animals in a dose of 1250 mg/kg (1/2 LD50). In the second series the suspension of acetaminophen in 2 % starch solution in a dose of 55 mg/kg was given. Non-genetic form of experimental type 2 diabetes mellitus was modeled by a single intraperitoneal administration of streptozotocin solution in doses 65 mg/kg, which was diluted by citrate buffer (pH 4.5) with the previous intraperitoneal nicotinamide administration in doses of 230 mg/kg. Rats, which were given the same amount of solvent (citrate buffer pH 4.5), were used as the control group. Results and discussion: Content of middle mass molecules and erythrocyte intoxication index were determined for research of endogenous intoxication status of rats with type 2 diabetes at single administration of acetaminophen. The experimental results show, that all investigated parameters changes compared with intact animals after acetaminophen administration to animals with type 2 diabetes. Aminotransferases are the main enzymes of protein metabolism and combine carbohydrate metabolism. The high levels of these enzymes in the blood are signal of liver tissues damages. The destruction and death of cells in this organ is accompanied by the release of enzymes in the blood. Conclusion: After analyzing of the obtained results, it can be argued that acetaminophen changes of endogenous intoxication indices and status of plasmatic membranes in rats with type 2 diabetes mellitus.